Co-designing a multi-criteria approach to ranking hazards to and from Australia’s emerging offshore blue economy - Mischa P. Turschwell; Christopher J. Brown; Myriam Lacharité; Jess Melbourne-Thomas; Keith R. Hayes; Rodrigo H. Bustamante; Jeffrey M. Dambacher; Karen Evans; Pedro Fidelman; Darla Hatton MacDonald; Ingrid Van Putten; Graham Wood; et al. (Environmental Science & Policy, 2023)

A network approach to analyse Australia’s blue economy policy and legislative arrangements - Miguel Frohlich; Pedro Fidelman; Ian Dutton; Marcus Haward; Brian W. Head; Dianne Maynard; David Rissik; Joanna Vince (Marine Policy, 2023)

The future of ocean governance - Bianca Haas; Mary Mackay; Camilla Novaglio; Liam Fullbrook; Michael Murunga; Carla Sbrocchi; Jan McDonald; Phillipa C. McCormack; Karen Alexander; Maree Fudge; Lyn Goldsworthy; Fabio Boschetti; et al. (Reviews in Fish Biology and Fisheries, 2022)

Mitochondrial DNA Profiling to Combat the Illegal Trade in Tortoiseshell Products - Erin L. LaCasella; Michael P. Jensen; Christine A. Madden Hof; Ian P. Bell; Amy Frey; Peter H. Dutton (Frontiers in Marine Science, 2021)
Hawksbill turtles ( Eretmochelys imbricata ) are exploited for their beautiful shell known as tortoiseshell or bekko, making them extremely vulnerable in the illegal global trade of tortoiseshell products. In this study, we developed an effective, standardized method using a commercially available kit to extract DNA and obtain informative mitochondrial DNA (mtDNA) control region sequences (~800 bp) from hawksbill turtle products in order to trace the sample back to a likely stock origin. We also sequenced additional skin samples from nesting beaches of Milman Island, Australia and Arnavon Island, Solomon Islands to add to the baseline data for hawksbill turtles in the Indo-Pacific. Our results indicate that nine of the 13 tortoiseshell products obtained from Papua New Guinea and Solomon Islands were from turtles with haplotypes found primarily at the Solomon Islands rookery and did not match those from nesting populations in Australia or SE Asia, with the exception of one haplotype also found in 3% of turtles at Milman Island. We also found that 23% of the market samples have haplotypes only documented in foraging populations, which illustrates the urgent need for more extensive sampling of rookeries to fill gaps in the reference baseline database. Nevertheless, our study results demonstrate an effective methodology for obtaining DNA of sufficient quantity and quality from hawksbill turtle products.